Gay vs. straight? Implications of intergroup perceptions on minority stress and the mental health of lesbian and gay people - Aybar Camposano, G.; Rodrigues, D. L.; Moleiro, C. (Current Psychology, 2024)
Lesbian and gay (LG) people overwhelmingly report higher rates of mental health disorders than their heterosexual counterparts due to living in homophobic contexts. However, little attention has been given to how LG people perceive their identity and group under said conditions. In this study, we used social identity theorizing to understand if minority stress and LG people’s perception of the status and boundaries between their ingroup, the LGBTQ + community vs. the heterosexual outgroup, worsens or improves mental health outcomes. A sample of 202 LG people from the United Kingdom responded to an online survey through Clickworker between January and March 2022. A three-step hierarchical linear regression showed that LG people experiencing higher minority stress reported adverse mental health outcomes. Additionally, LG people with elevated minority stress conveyed worse mental health outcomes when they perceived the group status between their LGBTQ + ingroup and heterosexual outgroup as either stable or illegitimate. Our findings suggest that adverse mental health outcomes among LG are explained by minority stress and how they perceive their identity within a broader social context. Our results propose tackling homophobic conditions while also challenging the perceived stability and illegitimacy of the LGBTQ + community by supporting its spaces and members.